An analysis on thematic progression of “World Heritage Ujung Kulon National Park” by UNESCO - Aziz Nala Ardhi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
Thematic progression is when the meaning of the last theme or rheme is carried over into the next theme or rheme. Also goes into more detail about how themes can change either by "coincidence," with new ideas coming out of the text, or in a way that makes sense, which is called a "thematic progression”. The focus of this study is on the analysis of thematic progression patterns revealed in the UNESCO article "World Heritage Ujung Kulon National Park." This study looks at how theme progression patterns can help grow and progress a text into a structured piece that can represent information or express the author's message. This research was made in a qualitative way because the data did not need to be analyzed statistically. The findings from the thematic progression investigation for “WORLD HERITAGE UJUNG KULON NATIONAL PARK” BY UNESCO are: (1) four types of thematic progressions are used in six business texts with different occurrences and percentages, (2) of the four types of thematic progressions used, the most dominant thematic progression pattern used is the constant thematic progression pattern with 19 occurrences and a percentage of 54%. Based on the analysis, the differences in the appearance of types of thematic progressions are used to make variations in the delivery of the message in the article so that it is easier for readers to understand the message.